Sikap Gotong Royong dari Tradisi Wiwitan pada Masyarakat Desa Condong Sari Kabupaten Purworejo - Siti Susilaningtyas; Elsa Putri Ermisah Syafril (UM Purwokerto Press, 2022)
Condongsari Village is a village located in Krajan Hamlet, Banyuurip District. The majority of Condongsari Village is an agricultural area. There is one tradition in Condongsari Village that is related to agrarian conditions and is still maintained today, namely the wiwitan tradition. Therefore, the objectives of this study are: (1) to explain the mutual cooperation attitude of the Condongsari Village Community in Purworejo; (2) to explain the mutual cooperation attitude of the Wiwitan Tradition in the Condongsari Village Community of Purworejo; (3) to know the reasons for the mutual cooperation attitude of the Wiwitan Tradition in the Condongsari Purworejo Village Community that still persists. This research includes qualitative research. Primary data sources came from informants, namely: farmers in the village of Condongsari, village elders, community leaders, village heads, young people. Secondary data sources are archives, photographs, videos and document studies that can support the focus of the study. The steps of data analysis include: data collection, data reduction, data tabulation, analysis of tabulated data using qualitative descriptive techniques, data presentation, and drawing conclusions. The results of this study are: (1) the attitude of mutual cooperation of the Condongsari Purworejo Village Community can be seen from various community activities, ranging from birth ceremonies, weddings, death ceremonies (measurements), village clean up, and other village traditional ceremonies. (2) The mutual cooperation attitude of the Wiwitan Tradition in the Condongsari Village Community in Purworejo can be seen from the preparation, the provision of materials (uborampe), to the Wiwitan tradition process. (3) The reason for the mutual cooperation attitude of the Wiwitan Tradition in the Condongsari Purworejo Village Community still persists because people still think that this tradition is a legacy from their ancestors and is a noble culture from generation to generation and has meaning as an expression of gratitude to God Almighty. The mutual cooperation attitude of the Wiwitan Tradition can be a source of knowledge to shape the cooperative character of students.